FAKTOR-FAKTOR YANG MEMPENGARUHI TAX COMPLIANCE DENGAN ADOPSI E-TAX SYSTEM SEBAGAI VARIABEL MEDIASI - Linda Santioso (Ultimaccounting Jurnal Ilmu Akuntansi, 2022)
Abstract - Tax revenue is often not achieved, research in Botswana states that taxpayer attitudes affect taxpayer compliance, research in Uganda Adoption of the E-tax System can mediate the effect of Attitude on the E-tax system. Can the above research be implemented in Indonesia so that the tax target can be achieved? This study aims to provide evidence of empirical influence between attitudes and attitudes of taxpayers to the e-tax system on tax compliance with the application of the e-tax system as a mediating variable. This study uses respondents who found 100 mandatory taxes in DKI Jakarta. The data used is primary data in the form of questionnaires distributed to individual taxpayers in Jakarta. Data processing in this study using the Smart Pls3 program. The results of the study are the attitude of taxpayers towards the implementation of the e-tax system, the attitude of taxpayers to tax compliance has a positive and significant effect, attitudes towards the e-tax system towards the implementation of the e-tax system, attitudes towards the e-tax system towards tax compliance have a positive effect. but not significant. While the mediation of the implementation of the e-tax system on the attitude of taxpayers towards tax compliance, the mediation of the application of the e-tax system on attitudes towards tax compliance e-mediates positively but not significantly. From the empirical results above, it shows that with the implementation of the e-tax system, it has an influence on the attitude of taxpayers who master technology where taxpayers become more obedient because it is easier and more efficient to pay taxes. Meanwhile, the behavior of taxpayers towards the implementation of the e-tax system, although there are positive results, has not given maximum results to tax revenues because many taxpayers also have difficulty learning the e-tax system, fearing they will make mistakes. The government is imposing too much on the implementation of the e-tax system in a hurry and some people are not ready so that the e-tax system, although positive for the future, is currently not having a significant impact. Keywords: Attitude of Taxpayers; Application of the Electronic Tax System; Behavior towards the Electronic Tax System; Tax Compliance